Corporate Governance and Business Ethics in Saudi Arabia Listed Banks: An Accountability Perspective - Alamri, Maree Ali; Alshekmubarak, Ibraheem ahmed (Journal of Accounting Research, Organization and Economics, 2023)
Objective This research explores the relationship between corporate governance and business ethics in Saudi-listed banks using an accountability framework by examining the perceptions of key stakeholder groups.Design/Methodology Using primary data from a distributed questionnaire survey to the various stakeholders within the banking sector of the Saudi Stock Exchange, 323 questionnaires were distributed with a final sample of 135 participants. The data were analyzed using non-parametric tests.Results This study revealed that there all Saudi-listed banks have their own codes of business ethics. The findings show that there is a strong perceived relationship between corporate governance and business ethics, which has a positive impact on the banks practices. Despite the practical weakness in Saudi banks internal context systems in that the lack of an official code, any meaningful developments in ethical standards will require mandating of the key principles in order to foster an effective corporate governance system and encourage Islamically-ethical business practices.Novelty/Originality This paper contributes to corporate governance and business ethics literature by providing a unique view from an accountability perspective.